Szkolenie i doskonalenie pracowników jako istotny element motywowania w aktualnych uwarunkowaniach firm - Kopertyńska, Maria Wanda (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
The article discusses issues related to employee training and development. It argues that trainingand development have significant impact on employee motivation. It is also one of the key elements of acompany's success. The issues discussed in the article are mainly based on research. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1184, s. 349-356